Analisis Rasio Likuiditas dalam Mengukur Kinerja Keuangan PT. Matahari Departement Store - Nisrina, Ulfah Laila (Jurnal Ilmiah Manajemen & Kewirausahaan, 2025)
This study aims to analyze the liquidity performance of PT Matahari Department Store Tbk during the 2021–2023 period by evaluating five key liquidity ratios: current ratio, quick ratio, cash ratio, cash turnover, and inventory to net working capital. Liquidity is essential for retail companies because daily operational activities—such as inventory purchases, employee salaries, store rental payments, and obligations to suppliers—require adequate short-term financial capability. This research employs a descriptive quantitative approach using secondary data obtained from the company’s annual financial statements. The results indicate that the company’s liquidity condition is generally weak and falls below the standard benchmarks of the retail industry in Indonesia. The current ratio and quick ratio show a consistent decline, reflecting the company’s inability to cover its short-term liabilities with available current assets, and highlighting increased dependence on inventory, which cannot be immediately converted into cash. The cash ratio also remains far below the ideal level, demonstrating limited cash reserves and a reliance on daily operating inflows to meet short-term obligations. Despite these weaknesses, the cash turnover ratio shows a continuous improvement each year, indicating efficient utilization of cash to generate sales. However, this efficiency has not been sufficient to address the negative net working capital condition caused by higher current liabilities compared to current assets. verall, the study concludes that PT Matahari Department Store Tbk faces significant liquidity challenges, and improvements in working capital management are necessary to ensure financial stability and business continuity.